2002
DOI: 10.1590/s0041-87812002000500007
|View full text |Cite
|
Sign up to set email alerts
|

Nail manifestations in pemphigus vulgaris

Abstract: Nail involvement in pemphigus vulgaris is rare. We describe 5 patients with pemphigus vulgaris presenting nail involvement. In this disease, nail manifestations present, by order of frequency, as chronic paronychia, onychomadesis, onycholysis, Beau's lines and trachyonychia. All our 5 cases presented with paronychia, and 1 of them also had Beau's lines. Treatment with prednisone and/or cyclophosphamide controlled mucocutaneous and nail manifestations in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
12
1
1
Order By: Relevance
“…12 Moreover, the association of methotrexate, dicloxacillin, oral steroids, and periodic intralesional corticosteroid injections were effective in a relatively resistant scalp disease. 13 The vermillion and nail involvement, as well as the verrucous, hyperkeratotic acral plaques seen in this patient were also described in other cases of pemphigus vulgaris\vegetans, [6][7][8] and these should be considered, together with the classical vegetant lesions in the skin folds, characteristic of the verrucous variant of this condition. …”
Section: Letter To the Editors Pemphigus Vegetans Associated With Versupporting
confidence: 56%
“…12 Moreover, the association of methotrexate, dicloxacillin, oral steroids, and periodic intralesional corticosteroid injections were effective in a relatively resistant scalp disease. 13 The vermillion and nail involvement, as well as the verrucous, hyperkeratotic acral plaques seen in this patient were also described in other cases of pemphigus vulgaris\vegetans, [6][7][8] and these should be considered, together with the classical vegetant lesions in the skin folds, characteristic of the verrucous variant of this condition. …”
Section: Letter To the Editors Pemphigus Vegetans Associated With Versupporting
confidence: 56%
“…Moreover, Cahali et al (2002) reported that no patient exclusively displayed toenail alterations in their series of five PV patients, whereas we observed 5 patients with toenail alterations exclusively and 4 patients with only fingernail affliction.…”
Section: Discussioncontrasting
confidence: 44%
“…Cahali et al (2002) reported S. aureus positive cultures in 2 out of 5 PV patients and paronychia was the primary nail alteration. Although S. aureus was the most common bacteria in our PV patients, bacterial cultures also demonstrated the presence of other organisms.…”
Section: Discussionmentioning
confidence: 96%
“…idiopathic thrombocytopenia) [9], ichthyosis vulgaris [10,11], immune dysregulation polyendocrinopathy enteropathy X-linked syndrome (IPEX) [12], immunoglobulin A deficiency [13], incontinentia pigmenti (Bloch-Sulzberger syndrome) [14], pemphigus vulgaris [15], primary biliary cirrhosis [16], reflex sympathetic dystrophy [17], and sarcoidosis [18,19]. However, for some of these cases, the clinical pictures show nail abnormalities that are different from trachyonychia (table 1).…”
Section: Resultsmentioning
confidence: 99%